RELATION OF MENTAL HEALTH AND COMMUNITY VIOLENCE IN YOUTHS - Gloria Margarita Gurrola Peña; Patricia Balcázar Nava; Oscar Armando Esparza del Villar; Norma Alicia Rubalcava; María Elena Rivera Heredia; Fuensanta López Rosales; Ma Dolores García Sánchez; Rafael Armando Samaniego Garay (European Scientific Journal, ESJ, 2014)
The purpose of this work was to determine the relationship that exists between being a contextual witness of acts of violence in the environments closest to university students, such as the area they live in, the school they attend, and the recreational places they frequent. In order to achieve this purpose, a scale of witness of community violence was drawn up and validated, which was applied along with the list of symptoms (SCL 90-R) to 1,465 students in 6 states of the north and center of the Mexican republic. The results indicate that the students have witnessed first hand acts of violence in the area they live in, their places of recreation, and finally in their school. Likewise, significant relations were seen between witnessing violence and symptoms of somatization, phobias, anxiety, interpersonal sensitivity, obsessive compulsive behaviors, and traits of psychoticism. The foregoing leads one to believe that violence not only turn those who suffer it directly into victims, but it also takes a heavy toll on the mental health of the contextual witnesses.